Modeling soil water movement and irrigation management strategies in jujube (Ziziphus jujuba) orchard using HYDRUS-1D - WANG, SHUIXIAN; MA, HAIYAN (The Indian Journal of Agricultural Sciences, 2014)
In Xinjiang, an arid region located in the north-western China, water use for irrigation of predominantly jujube (Ziziphus jujuba Mill.) is high whereas water use efficiency is low. Due to that, how to increase irrigation efficiency is highly concerned by the local agricultural authorities. To quantify the irrigation water deep leakage and soil water balance, water application, crop growth, and soil water dynamics were studied on a sandy loam, sandy, and clay field in the years 2010 and 2011. Research shows that the soil water model HYDRUS-1D can be used as a tool to simulate and quantify improved management strategies and update irrigation standards in this region. The parameters sensitivity analysis result showed that soil water bottom flux was sensitive to Î¸s and Ks in soil layers. The simulation results indicated that soil water leakage was influenced by soil texture, irrigation quota and irrigation frequency, and so on. In addition, soil water leakage was very serious under the traditional surface irrigation during jujube growth period. Soil water leakage mainly occurred in growth from mid-June to mid-August, which is the key period for jujube tree demand water, resulting in severe soil water leakage. Therefore, for improving the efficiency of irrigation water use and reducing the deep soil water leakage, it is not suitable to adopt surface irrigation in the study areas. Several different scenarios have been generated to better understand the effect of irrigation management on soil water leakage by HYDRUS-1D model in the study areas. The drip irrigation can reduce soil water leakage. Consequently, it should be recommend adopting drip irrigation technology, which would not only save water but also improve the efficiency of water use in the study areas.